Fuga de cérebros: proposta de um modelo de gestão do programa de doutorado pleno CAPES à luz da visão baseada em recursos - Santos, Sara Cristina Alves dos (2024)
Globalization and the networked society, with processes that transcend national borders, mark the beginning of the 21st century. These factors challenge Higher Education Institutions to internationalize in order to train high-level human resources, highlighting the need for the state to prioritize and encourage academic mobility. In Brazil, the Coordination for the Improvement of Higher Education Personnel (CAPES) is the primary funding agency for internationalization, enabling scholarship holders to pursue their full-time stricto sensu graduate studies abroad through the Full Doctoral Program. However, this can lead to brain drain when researchers do not return to their home country, causing losses. This dissertation investigates strategies to manage the CAPES Full Doctoral Program in light of the Resource-Based View (RBV), considering the issue of brain drain. The study aims to propose a management model for the Program based on RBV theory, which regards Human Resources as sources of sustainable competitive advantage. The research is qualitative in nature, with a descriptive approach and based on a single case study. Data collection included documentary research on the MEC/CAPES portal, data from the Sucupira Platform (GeoCAPES), semi-structured interviews with managers from the CAPES International Relations Directorate (DRI), students, and alumni of the Program, as well as semi-structured questionnaires with students, allowing data triangulation as per Yin (2001). The analysis followed the Content Analysis technique proposed by Bardin (2011). The main results indicate that, despite the return commitment established with CAPES in the Scholarship Award and Acceptance Agreement, some participating researchers do not return to Brazil due to a lack of resources, infrastructure, and political instability in the country; better salaries or scholarships abroad; participation in research groups at renowned universities; and negotiations with CAPES (novation). Data analysis led to the proposal of a Management Model that replaces the mandatory return period with the possibility of remote contribution through an Academic Activity Plan, ensuring impact and relevance equivalent to the investment made, thus promoting the absorption of research results in Brazil. For the effectiveness of the proposed Model, future studies are suggested to refine the Academic Activities with ad hoc consultants. This work contributes to the Sustainable Development Goals (SDGs 4, 8, 16, and 17), demonstrating its social impact.